Plasma metabolomic analysis indicates flavonoids and sorbic acid are associated with incident diabetes: A nested case-control study among Women's Interagency HIV Study participants. - Elaine A Yu; José O Alemán; Donald R Hoover; Qiuhu Shi; Michael Verano; Kathryn Anastos; Phyllis C Tien; Anjali Sharma; Ani Kardashian; Mardge H Cohen; Elizabeth T Golub; Katherine G Michel; et al. (PLoS ONE, 2022)
Introduction Lifestyle improvements are key modifiable risk factors for Type 2 diabetes mellitus (DM) however specific influences of biologically active dietary metabolites remain unclear. Our objective was to compare non-targeted plasma metabolomic profiles of women with versus without confirmed incident DM. We focused on three lipid classes (fatty acyls, prenol lipids, polyketides). Materials and methods Fifty DM cases and 100 individually matched control participants (80% with human immunodeficiency virus [HIV]) were enrolled in a case-control study nested within the Women's Interagency HIV Study. Stored blood samples (1-2 years prior to DM diagnosis among cases; at the corresponding timepoint among matched controls) were assayed in triplicate for metabolomics. Time-of-flight liquid chromatography mass spectrometry with dual electrospray ionization modes was utilized. We considered 743 metabolomic features in a two-stage feature selection approach with conditional logistic regression models that accounted for matching strata. Results Seven features differed by DM case status (all false discovery rate-adjusted q<0.05). Three flavonoids (two flavanones, one isoflavone) were respectively associated with lower odds of DM (all q<0.05), and sorbic acid was associated with greater odds of DM (all q<0.05). Conclusion Flavonoids were associated with lower odds of incident DM while sorbic acid was associated with greater odds of incident DM.